Relationship of lipoprotein-associated phospholipase A2 and oxidized low density lipoprotein in carotid atherosclerosis[S] - Kasey C. Vickers; Colin T. Maguire; Robert Wolfert; Alan R. Burns; Michael Reardon; Richard Geis; Paul Holvoet; Joel D. Morrisett (Journal of Lipid Research, 2009)
Plasma levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and oxidized low density lipoprotein (oxLDL) have been identified as risk factors for cardiovascular disease. Lp-PLA2 is the sole enzyme responsible for the hydrolysis of oxidized phospholipids on LDL particles in atherosclerotic plaques. We have studied the relationship between Lp-PLA2 and oxLDL in carotid endarterectomy (CEA) tissues and in matched plasmas. In extracts from CEA anatomical segments, the levels of oxLDL were significantly associated with the levels of Lp-PLA2 protein (r = 0.497) and activity (r = 0.615). OxLDL and Lp-PLA2 mass/activity were most abundant in the carotid bifurcation and internal segments where plaque was most abundant. In extracts from CEA atheroma, the levels of oxLDL and Lp-PLA2 were significantly correlated (r = 0.634). In matched plasma and atheroma extracts, the levels of Lp-PLA2 were negatively correlated (r = − 0.578). The ratio of Lp-PLA2 to oxLDL was higher in atheromatous tissue (277:1) than in normal tissue (135:1) and plasma (13:1). Immunohistochemical experiments indicated that in plaques, oxLDL and Lp-PLA2 existed in overlapping but distinctly different distribution. Fluorescence microscopy showed both oxLDL and Lp-PLA2 epitopes on the same LDL particle in plasma but not in plaque. These results suggest that the relationship between Lp-PLA2 and oxLDL in the atherosclerotic plaque is different from that in the plasma compartment.